Is Gen-Z Aware of the SatuSehat Platform as an Extension of the PeduliLindungi Application? : Branding Effects Model Approach - Verry Agusta; Dwi Anggia; Riska Yuliarosa (Jobmark: Journal of Branding and Marketing Communication, 2024)
The SatuSehat application is a connecting platform that integrates individual health data between health service facilities in electronic medical records, transforming PeduliLindungi. SatuSehat aims to create an integrated public health information system between all health facilities, such as hospitals, health centers, clinics, pharmacies, and laboratories connected through the Satu Sehat platform. Thus, creating a more unified and integrated digital health information ecosystem can help the government make better decisions and provide more effective services to the community. This article explores the brand awareness of the SatuSehat application from the perspective of Wijaya's AKIELS model with a qualitative case study method. The primary data source for the research is Generation Z from Bakrie University. Secondary data related to SatuSehat was obtained from Ministry of Health spokesperson Siti Nadia Tarmizi. Data collection was carried out using in-depth interviews, observation, and searching digital and scientific documents. The results show that the SatuSehat application is still at the brand recognition stage because the respondents recognized the brand after receiving reminders via assistance. In this case, informants first remembered the PeduliLindungi application before mentioning the SatuSehat application.